A Review of Current Conceptual Research on Short Stories Use in EFL Classrooms - Pardede, Parlindungan (JET (Journal of English Teaching), 2021)
Literature use in EFL learning and teaching has regained great attention in the last decades, and among all literary genres, short stories are regarded the most effective to fuse in EFL classrooms. Conceptual research exploring the use of short stories has significantly increased. However, reviews identifying the insights and ideas concerning the what, why, and how of using short stories in EFL classrooms in these articles are still rare. Thus this paper aimed to review 14 conceptual research published in 2011-2020 and indexed in Google Scholar focusing on short stories use in EFL learning and teaching to draw a general picture of the underlying reasons and difficulties in using short stories, considerations for selecting short stories, and how to exploit short stories in the classroom. Based on the analysis employing the constant comparative method, this paper reports the results. After discussing the findings, some suggestions are recommended.